Analisis Strategi Promosi Dalam Meningkatkan Jumlah Peserta Didik Pada SMK Pati Di Rantelemo - Patadungan, Ellyn; Bandaso, Srysetyawanie (UKI Toraja Press, 2022)
The purpose of this study was to determine the promotion strategy in increasing the number of students at SMK Pati Rantelemo. This research method uses a qualitative descriptive type of research that is to provide evidence of truth according to the theory and issues raised through observation, interviews and documentation. The types of data used are primary data and secondary data, then analyzed according to the theory of Milles, Huberman and Saldan, namely: data reduction, data presentation, and conclusions and verification. Based on the results of the research that has been done, it can be seen that the promotional strategy carried out by SMK Pati Rantelemo in increasing the number of students has been carried out as much as possible, using the concept of a promotional mix, namely Advertising which includes (billboards and brochures), Sales Promotion (free entry fees and registration fee), Individual Sales (all school members participate in promoting the school), Publicity/Community Relations which includes (holding outreach to nearby churches), and Direct Selling (listing the school's telephone number on brochures and banners).